2021
DOI: 10.1111/eth.13218
|View full text |Cite
|
Sign up to set email alerts
|

Female Western Australian magpies discriminate between familiar and unfamiliar human voices

Abstract: The ability to recognize familiar and unfamiliar individuals is important as it plays a central role in many social interactions. Previous research has found that some animal species can discriminate among conspecifics, and recent findings indicate that some species are also able to discriminate among heterospecifics, including humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The ability to discriminate between extra-group and intra-group conspecifics based on vocal cues is likely to be highly beneficial for Western Australian Magpies. As a territorial species that defends stable territories yearround and participates in frequent intergroup interactions (Hidayat 2018, Dutour et al 2021, being able to recognize and respond appropriately to the territorial calls of different groups of individuals is likely to reduce the energetic and physical costs associated with territorial defence and intergroup interactions (Temeles 1994, Lambrechts & Dhondt 1995, Tibbetts & Dale 2007. Previous work has found that Western Australian Magpies respond differently to the alarm calls of reliable callers (those whose alarm call had previously been played during a predator presentation) compared with unreliable callers (those whose alarm call had previously been played in the absence of a predator) (Silvestri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to discriminate between extra-group and intra-group conspecifics based on vocal cues is likely to be highly beneficial for Western Australian Magpies. As a territorial species that defends stable territories yearround and participates in frequent intergroup interactions (Hidayat 2018, Dutour et al 2021, being able to recognize and respond appropriately to the territorial calls of different groups of individuals is likely to reduce the energetic and physical costs associated with territorial defence and intergroup interactions (Temeles 1994, Lambrechts & Dhondt 1995, Tibbetts & Dale 2007. Previous work has found that Western Australian Magpies respond differently to the alarm calls of reliable callers (those whose alarm call had previously been played during a predator presentation) compared with unreliable callers (those whose alarm call had previously been played in the absence of a predator) (Silvestri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…feed urban-dwelling animals (e.g., Marion et al, 2008), while others may persecute them (e.g., Harris, 1984). Previous work has demonstrated that wild Australian magpies (Gymnorhina tibicen dorsalis) and captive carrion crows (Corvus corone corone) are able to discriminate between voices of familiar and unfamiliar humans (Wascher et al, 2012;Dutour et al, 2021). Thus, some bird species may discriminate between threatening and non-threatening humans using acoustic cues.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that cues in other sensory modalities, such as auditory cues, are used as indicators of human risk (e.g., Lynch et al, 2015). For example, wild animals may discriminate between familiar and unfamiliar human voices (McComb et al, 2014;Dutour et al, 2021). Yet, the majority of research on animals' perception of human auditory cues to assess human risk has been conducted on captive and domesticated animals (Adachi et al, 2007;Lampe and Andre, 2012;Proops and McComb, 2012;Wascher et al, 2012;Saito and Shinozuka, 2013;Ratcliffe et al, 2014;Leroux et al, 2018), while little is known about wild urban-living animals.…”
Section: Urban Gulls Show Similar Thermographic and Behavioral Respon...mentioning
confidence: 99%
“…During playback experiments, the two experimenters stood ∼10-13 m from the speaker. The birds were habituated to the presence of these two experimenters (Dutour et al, 2021c). One observer was assigned to soundtrack operation and used a food reward to lure other group members away from the testing area, while the other observer videotaped the behaviour of the focal magpie using a digital video recorder (Panasonic HC-V520 M).…”
Section: Playback Protocol and Response Variablesmentioning
confidence: 99%
“…We measured four behaviours: (1) time spent vigilant 20 s before and after playbacks; recorded when birds demonstrated an erect posture and were actively scanning their surroundings, (2) the latency to resume normal (non-vigilant) behaviour, (3) production of alarm calls, and (4) fleeing behaviour; individuals that fled more than 10 m after the start of the playback. We measured these behaviours because they are commonly used indicators of perceived danger in magpies (Pell et al, 2018;Igic et al, 2019;Silvestri et al, 2019;Dutour et al, 2021c). Calling and fleeing behaviours were very rare (8 out of 96 playbacks in total) and thus could not be used for statistical analysis.…”
Section: Playback Protocol and Response Variablesmentioning
confidence: 99%